The Paradox of Emotional Proximity Paradox: Why Children Are More Open to Others Than Their Parents - Firdausi R. Nisa; Siska Adinda Prabowo Putri; I. Rheny Arum Permatasari; Lucy Hariadi; Dessy Pratiwi; Tri Amelia Rahmitha Helmi; Wafa Sofia Fitri (Jurnal Berkala Kesehatan, 2025)
The paradox of emotional proximity in modern family dynamics occurs when children are more open to external parties than their own parents. This research aims to synthesize the factors underlying this phenomenon and its implications for family communication in the digital era. Using a Systematic Literature Review (SLR) guided by the PRISMA protocol, systematic searches were conducted on Scopus, SINTA, and Google Scholar databases (2000–2025). From 537 identified records, 7 primary studies met the inclusion criteria and were analyzed using thematic synthesis. Results show that child openness is primarily determined by perceived relational safety rather than interaction frequency. Authoritarian parenting and emotional suppression were found as main inhibiting factors, while peers and digital platforms provide a more democratic space for identity negotiation. The synthesis reveals that children manage privacy boundaries selectively, where boundaries toward parents become stricter as a form of self-protection. This research suggests a parenting transition towards emotion coaching, prioritizing empathy and validation over mere technical problem-solving to overcome the paradox.